La Lucrècia Borja de ficció en el drama d'Hugo i els seus derivats. - CALATAYUD, MARC GOMAR (Scripta)
The Victor Hugo's drama Lucrezia Borgia gives to the historical character some attributes in line with the sensationalist preferences of that time: being a female, powerful, beautiful and educated. Lucrezia Borgia is the best example of what Kristeva names µthe abject» in Pouvoirs de l'horreur (1980). The character is a femme fatale image linked to poison or incest and it was popularized thanks to the many works resulting from this drama. So that, the features of the fictional character prevailed to the real historical character in the popular beliefs, this happened in Donizetti's opera, but also in the chapbooks of that time. Lucrezia Borgia had previously been considered an instrument in the service for family policies, but she became part of an evil triangle, thanks to her own attitude, along with her brother, Cesare Borgia, and her father, the pope Alexander VI.